Level of Public Awareness in Protecting the Environment in Pantai Cermin Kanan Subdistrict - Azzahra, Fatimah; Nanda, Meutia; Nasution, Dinda Azria; Aisyah, Siti Nur; Pohan, Rahmaida (Universitas Ibn Khaldun Bogor, 2024)
Because many people do not understand the importance of protecting the environment, public awareness of the condition of the surrounding environment is still very low. As a result, many people continue to throw garbage in the wrong place, causing a lot of household waste to pollute the environment. In Pantai Cermin Kanan Village, there is a problem of low environmental awareness. The purpose of this study was to determine the level of public awareness of environmental management in Pantai Cermin Kanan Village. This study applies quantitative descriptive. Because the study population was 1,212 families, 92 families were taken as random samples using non-probability sampling techniques. The results of the study showed that people who sometimes litter were 54.3%, the most people who did not process waste were 76.6%, and the lack of community participation in farming (58%). This study found that people in Pantai Cermin Kanan Village were less aware of the importance of farming, waste processing, and protecting the environment. It is recommended that the local government and the private sector work together to improve public socialization and education about the importance of protecting the environment, managing waste, and farming. The majority of people still litter and do not process waste (58%). The conclusion of this study is that the level of public awareness in protecting the environment, waste management, and farming in Pantai Cermin Kanan Village is still low. The majority of people still litter, do not process waste, and are not active in farming, it is recommended to the local government and collaboration with the private sector to increase socialization and education to the community about the importance of protecting the environment, waste management, and the benefits of farming.